9.9k views
5 votes
Somebody please help me with this ASAP I need the answers to the whole thing!! Please

Somebody please help me with this ASAP I need the answers to the whole thing!! Please-example-1
User Kuanyui
by
4.7k points

1 Answer

7 votes

Answer:

(-2, 3 )

(-1, 2
(1)/(2))

(0, 2)

(1, 1
(1)/(2))

(2, 1)

Explanation:

You just simply substitue the values given into the equation, and the answer worked out will be the value of y.

a = -
(1)/(2) × -2 + 2 = 1 + 2 = 3

b = -
(1)/(2) × -1 + 2 =
(1)/(2) + 2 = 2
(1)/(2)

c = -
(1)/(2) × 0 + 2 = 0 + 2 = 2

d = -
(1)/(2) × 1+ 2 = -
(1)/(2) + 2 = 1
(1)/(2)

e = -
(1)/(2) × 2+ 2 = -1 +2 = 1

Hope this helps you :)

User Semion
by
4.4k points